Breeding value of potato hybrid clones from the VIR collection revealed in the environments of Kamchatka Territory - A. D. Ivashchenko; T. P. Sherstyukova; O. I. Khasbiullina; E. V. Rogozina (Труды по прикладной ботанике, генетике и селекции)
Background. Potato breeding involves planned artificial hybridization between previously selected parental lines. A way to make potato breeding more efficient is to use the diversity of the germplasm and broaden the gene pool of parental lines. Interspecific potato hybrids originated on the elite potato germplasm display a set of valuable traits. The current challenge is to assess the performance of potato hybrids under specific soil and climate conditions to clarify their breeding value.The objective of the study was to evaluate potato hybrids in the environments of Kamchatka Territory according to a set of traits, identify the best parental lines, develop new hybrid combinations, and select promising breeding material.Materials and methods. Eleven potato hybrids from VIR were studied over three years (2020–2022) in the fields of Kamchatka Research Institute of Agriculture. The hybrids were benchmarked against two reference potato cultivars, ‘Fresco’ and ‘Vulkan’, belonging to the early and mid-early maturity groups, respectively. Crosses between the hybrids and 28 potato cultivars were carried out in the greenhouse. The new hybrid material was tested in a preliminary trial nursery for yield and earliness.Results. Hybrid 117-2 was better in yield (899 g/plant) than cvs. ‘Vulkan’ and ‘Fresco’ (700–739 g/plant). Hybrids 94-5, 99-10- 1, 8-1-2004, 8-3-2004, 8-5-2004, 135-3-2005, 135-5-2005, 99-6-6, and 134-2-2006 in most traits matched the potato cultivars, manifesting good berry formation and seed setting when crossed. Out of 140 crosses between 11 hybrids and 28 cultivars, 35 crosses between 10 hybrids and 13 cultivars were successful. Most hybrids were effectively used in crossings as maternal forms.Conclusion. VIR’s hybrids 94-5, 8-1-2004, and 8-5-2004 proved the most promising as source material for the development of new early potatoes under the conditions of Kamchatka Territory.